التعليم في السليمانية عاصمة مملكة كوردستان الجنوبية في عهد الملك محمود البرزنجي 1591-1881 (The Development of Education at the capital city of Suleymaniye, North Kurdistan during the period of Sheikh Mahmud Al-Barzanji 1811-1956) - Abdul Hamid, Faisal@Ahmad Faisal; Mohd Nor, Mohd Roslan; Rashid, Kamal Taher (Journal of Al-Tamaddun, 2014)
This article discusses the history of the formation of the Kurds and Kurdistan, mainly regarding the development of Islamic education in Kurdistan and a number of renowned Islamic scholars in the era of Sheikh Mahmud al-Barzanji. It also examines on existing educational institutions in the capital city of Suleymaniye, Kurdistan, the history of the development of Kurds nation and Kurdistan state around 1918-1925 and the contribution of education and development that occurred with special focus on contribution by Sheikh Mahmud al-Barzanji.